Video: Leadership in Spaces and Places - Salovaara, Perttu (Organizational Aesthetics, 2014)
Link to the film: https://vimeo.com/95709554 The physical materiality of workplaces and spaces is easily overlooked and taken for granted - as something that is just there, as a backdrop of other, more important issues. In its simplest form spaces and places lead in very explicit ways: we follow corridors, climb stairs, open doors and cannot walk or talk through the walls. Self-service restaurants, streets, paths, airports and other public spaces lead people, too. The documentary film Leadership in Spaces and Places asks the question "how do spaces and places perform and construct leadership?" The film was shot in twelve different locations, ranging from Microsoft and a real estate agency to a church, a theatre and a historic dry-dock. In each of the places the question was: How do places lead? Today, leadership is not only attached to persons, but also to physical materiality: spaces, places, buildings, cities, materials and artefacts. People seem to know what to do even when there is no one telling them what to do. Places and spaces have that effect. Examples of questions we came across in these various spaces: What kind of images children might attach to a closet door that is left open when they go to bed? Can physical architecture in a church lead people’s emotions? How does the physical space in theatre, like stage and green room, affect an actor? Building a traditional wooden ship, what does a ship-builder pay attention to? What kinds of values are attached to preserving an old service elevator? What leads an urban explorer to visit deserted, abandoned houses?